2019
DOI: 10.1155/2019/6380801
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Variant Anatomy of the Circle of Willis and Association with Vascular Anomalies on Cerebral CT Angiography

Abstract: Background and Purpose. There is a wide variation in the anatomy of the CW in different individuals and population groups. The purpose of this study was to determine the proportion of variant anatomy of the circle of Willis (CW) and associated anomalies in patients with suspected cerebrovascular disease referred for cerebral computed tomography angiography (CTA) in two tertiary hospitals in Kenya. Methodology. This was a cross-sectional descriptive study conducted on 94 patients referred for cerebral CTA at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 31 publications
7
11
0
2
Order By: Relevance
“…Adult type circulation was found in 105 patients (83.3%), with fetal circulation identified unilaterally in 11.1% of cases, and bilaterally in 5.6% of cases, a finding that is congruent with literature studies [15,19,24]. In the evaluation of adult vs fetal type circulation, that relies on deciding whether the posterior communicating artery is larger than the precommunicating segment of the posterior cerebral artery, some studies cite a third variant called transitional, where the two arteries are identical in size; however, we did not take this option into consideration, as we considered that it can introduce bias due to the limits in accurately comparing the vessel diameters, where the imaging plane, resolution and scale, blood flow, and imaging software may influence the measurements.…”
Section: Discussionsupporting
confidence: 88%
“…Adult type circulation was found in 105 patients (83.3%), with fetal circulation identified unilaterally in 11.1% of cases, and bilaterally in 5.6% of cases, a finding that is congruent with literature studies [15,19,24]. In the evaluation of adult vs fetal type circulation, that relies on deciding whether the posterior communicating artery is larger than the precommunicating segment of the posterior cerebral artery, some studies cite a third variant called transitional, where the two arteries are identical in size; however, we did not take this option into consideration, as we considered that it can introduce bias due to the limits in accurately comparing the vessel diameters, where the imaging plane, resolution and scale, blood flow, and imaging software may influence the measurements.…”
Section: Discussionsupporting
confidence: 88%
“…[8][9][10][11][12][13][14][15] Our findings on the frequency of fPCA are in accordance with most previous studies, which found fPCA in around 20-30% of cases. 9,[15][16][17][18][19] The higher frequency of fPCA on the right side found in our study was also reported by two earlier studies in populations with cerebrovascular diseases. 9,16 In line with earlier studies, we found a lower frequency of vCoW in the anterior circulation compared to the posterior circulation.…”
Section: Discussionsupporting
confidence: 91%
“…The anatomical variability of the patterns of the circle of Willis in different ethnic and racial groups is frequently disputed by authors. Although some authors have found no evidence of differences in various populations [4], others describe certain prevalence of one vascular pattern over the other in studied cohorts [3] [5] [7]. Comparison of the data obtained by authors from the different populations shows that all segments of the cerebral arterial ring were well developed in 37.2% of patients in Kenya, 28.4% of individuals in Iran, and only in 14.5% of the studies group in France (Table 4).…”
Section: Discussionmentioning
confidence: 70%
“…The review of literature shows that the complete arterial ring develops only in 14.5% -37% of individuals, and vascular components of CW exhibit a wide range of anatomic variations [3] [4] [5] [6]. In their extensive study on 507 samples, Chen et al [4] classified variations of the anterior and posterior parts of the CW by twenty types based on unilateral and bilateral hypoplasia or aplasia of each contributing vessel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation